Guilty Knowledge, Guilty Pleasure : the Dirty Art of Poetry. - Logan, William, 1950 November 16- (Columbia University Press, 2014)
William Logan has been a thorn in the side of American poetry for more than three decades. Though he has been called the?most hated man in American poetry," his witty and articulate reviews have reminded us how muscular good reviewing can be. These new essays and reviews take poetry at its word, often finding in its hardest cases the greatest reasons for hope. Logan begins with a witty polemic against the wish to have critics announce their aesthetics every time they begin a review.?The Unbearable Rightness of Criticism" is a plea to read those critics who got it wrong when they reviewed Lyr.